2019
DOI: 10.1007/s41999-018-0154-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition education on malnutrition in older adults in European medical schools: need for improvement?

Abstract: Purpose Malnutrition is a condition which is highly prevalent, especially in older persons. Physicians play an important role in multidisciplinary nutritional management, but often feel inadequately prepared to provide nutritional information/therapy to their patients. The aim of this study was to gather information on curricular content on malnutrition in older persons in basic study programs for medical doctors. Methods We selected a cross-sectional study design and used a Web-based online survey. We emailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…26,29 Malnutrition training is not currently included in nutrition courses taught at nearly 30% of European educational institutions for nurses. 30 A Delphi study among Dutch GPs showed that the top three nutrition topics were diabetes mellitus, hypercholesterolaemia, and obesity, whereas nutrition specific to older people ranked as lower priority. 31 This reflects the historical focus in medical training where nutrition education has been traditionally used for the prevention of cardiovascular disease.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…26,29 Malnutrition training is not currently included in nutrition courses taught at nearly 30% of European educational institutions for nurses. 30 A Delphi study among Dutch GPs showed that the top three nutrition topics were diabetes mellitus, hypercholesterolaemia, and obesity, whereas nutrition specific to older people ranked as lower priority. 31 This reflects the historical focus in medical training where nutrition education has been traditionally used for the prevention of cardiovascular disease.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Malnutrition in older adults has a multifactorial aetiology, is highly prevalent and associated with reduced quality of life and an increased mortality risk; yet, it can be prevented and treated through nutritional therapy [ 25 ]. In most European countries, doctors are responsible for prescribing nutritional therapy and referring older adults to dieticians [ 25 ]. Yet, only a few European medical schools include nutrition in later life in undergraduate medical curricula [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In most European countries, doctors are responsible for prescribing nutritional therapy and referring older adults to dieticians [ 25 ]. Yet, only a few European medical schools include nutrition in later life in undergraduate medical curricula [ 25 ]. Teaching on causes, assessment and consequences of malnutrition has been more frequently reported than that of perioperative nutrition or nutrition in intensive care units [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given that physicians of all specialties, with the exception of paediatrics, are involved in the treatment of care of older patients, it has been recognised that geriatric medicine should not be part of postgraduate training for specialty geriatricians alone, but should be part of undergraduate medical training for all future physicians. Several recent reviews demonstrate that there is still need for improvement, with key geriatric topics missing in many undergraduate curricula across Europe [ 40–42 ]. As an initial success, a European-wide consensus has been achieved for minimum requirements in undergraduate medical training [ 43 ].…”
Section: Undergraduate Trainingmentioning
confidence: 99%